NDVI dynamics and drivers in the Kalamaili Ungulate Nature Reserve: insights from an arid ecosystem in northwest China - Yan, Caiyu; Wang, Xu; Sun, Gang; Zhang, Lin; Han, Wei; Peng, Huangye; Luo, Linglv (Frontiers in Environmental Science, 2025)
The Kalamaili Ungulate Nature Reserve is a vital ecological unit and an important sanctuary for wild ungulates. Given its high sensitivity to climate change, understanding the dynamics of vegetation growth in the reserve is crucial for effective management and conservation efforts. This study assessed vegetation growth in the Kalamaili Ungulate Nature Reserve using NDVI and meteorological data from 2001 to 2022. A combination of methods, including Theil–Sen trend analysis, the Mann–Kendall test, the Hurst index, partial correlation analysis, lag time analysis, and multiple regression residual analysis, were employed to evaluate the response mechanisms of NDVI to climate change and human activities. The results showed that (1) NDVI in the reserve exhibited an increasing trend from 2001 to 2022, with a growth rate of 0.0002 per year, and NDVI values were generally higher in the western region than in the eastern region. (2) Temperature was the dominant factor influencing NDVI on both annual and growing-season scales, while precipitation had a greater effect on NDVI during the annual summer, autumn, and growing seasons. (3) The NDVI trend is projected to shift from an upward to a downward trend in the future, potentially affecting 59.16% of the reserve. (4) Temperature showed a two-month lag effect on NDVI, whereas precipitation had a one-month lag effect. (5) Residual analysis revealed that both climate change and human activities contributed to vegetation improvement, accounting for 55.69% of the observed changes. These findings emphasize the importance of ongoing vegetation monitoring in the Kalamaili Ungulate Nature Reserve. Given that the reserve lies within China’s arid northwestern region and is highly vulnerable to global warming, the results provide a scientific foundation for managing the reserve and developing sustainable strategies. They also offer valuable insights for research on similar desert ecosystems.